HUBUNGAN PERSEPSI BEBAN KERJA DENGAN STRES KERJA PADA PERAWAT IGD DAN ICU EKA HOSPITAL PEKANBARU - Heri ' Susanto; Bayhakki ' '; Arneli wati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract This study aimed to investigate correlation between perceotion workload and work stress in Emergency and ICU nurses in Eka Hospital Pekan Baru. This study using corelation method with cross sectional approach. Total samples were 46 respondents that recruited by total sampling techniques. Instruments  used were 35 questions of workload questionnaire and 35 questions of stress work questionnaire. Data analysis were univariate and bivariate with chi Square. Results of the study showed respondents with light workload perception with work stress were 44,4%,  55,6% with no work stress and had heavy workload with work stress were 53,6%,and 46,4% with no work stress. Result of statistic test showed p value was 0,5>α 0,05 it meant that there was no correlation between workload perception of and workstress. It is adviced  to  ICU and Emergency nurses to improve coping mechanism in dealing with stess at work. Keywords                : Perception of workload, work stress,emergency and icu nurses